Reg3A (regenerating family member 3 alpha) acts as a tumor suppressor by targeting DMBT1 (deleted in malignant brain tumors 1) in gastric cancer. Issue 1 (1st January 2021) - Wang, Liang; Tuo, Hongfang; Song, Zhe; Li, Wei; Peng, Yanhui
ABSTRACT: Regenerating family member 3 alpha (Reg3A) encodes a pancreatic secretory protein that may be involved in cell proliferation or differentiation. However, the function and downstream regulatory mechanism of Reg3A in gastric cancer (GC) remains elusive. This study aimed to clarify the function and mechanism of Reg3A regulating cell proliferation in GC. The expression levels of Reg3A were confirmed in GC patients and cells using qRT-PCR and western blotting. TCGA datasets and clinical samples were used to explore the correlation between Reg3A and clinicopathologic features in GC. Cell viability, colony formation, and xenograft tumorigenesis assays were performed to detect the function of Reg3A on cell proliferation. Besides, we predicted the correlated genes of Reg3A by analyzing TCGA datasets, and further investigated the downstream regulatory mechanism of Reg3A in GC. Our results demonstrated that Reg3A is down-regulated in vitro and vivo (P < 0.05). Reg3A expression are negatively correlated with TNM classification ( P < 0.001), lymph node ( P < 0.001) in GC. Reg3A significantly suppresses cell proliferation in GC (P < 0.05). Bioinformatic analysis and experimental results confirmed that Reg3A positively regulates the expression of deleted in malignant brain tumor 1 (DMBT1, P < 0.05). Besides, Reg3A and DMBT1 all prolong the overall survival (OS, P < 0.01), post-progression survival (PPS, P < 0.05), and first progression survival (FP, P < 0.01). The function of Reg3A inhibiting cell proliferation is abolished by DMBT1 siRNA in GC ( P < 0.05). In conclusion, Reg3A may act as a novel tumor suppressor by promoting DMBT1 expression, which may be a potential therapeutic target in patients with GC.